Major post-prostate biopsy complications under antibiotic augmentation prophylaxis protocol. (January 2022) - Rodrigues, Antônio Antunes; Muglia, Valdair; de Albuquerque, Emanuel Veras; Mori, Rafael Ribeiro; Feres, Rafael Neuppmann; Nogueira, André Beluso; e Almeida, Vanessa Soares de Oliveira; Freire, Guilherme Carvalho; Santos, Henrique Amorim; dos Santos, Sandra Conceição; Cologna, Adauto José; Tucci Jr, Silvio; et al.
Objective: To identify risk factors for major post-biopsy complications under augmented prophylaxis protocol. The risk factors already described mainly comprise outdated antibiotic prophylaxis protocols. Material and methods: This retrospective cohort study included patients that underwent transrectal ultrasound-guided biopsies, from 2011 to 2016. All patients had received antibiotic prophylaxis with ciprofloxacin and gentamicin. Patients were grouped according to the presence or absence of post-biopsy complications. Demographic variables and possible risk factors based on routine clinical assessment were registered. Correlation tests, univariate and multivariate analyses were used to identify risk factors for post-biopsy complications. Results: Of the 404 patients that were included, 25 (6.2%) presented 27 post-biopsy complications, distributed as follows: acute urinary retention ( n = 14, 3.5%), infections ( n = 11, 2.7%) and hemorrhage ( n = 2, 0.5%). On univariate analysis, patients who presented complications showed higher body mass index and post-voiding residual volumes. Multivariate analysis identified ethnicity and prostate-specific antigen (PSA) density as possible risk factors for biopsy complications. The presence of bacterial resistance identified by rectal swabs did not correlate with the incidence of complications and infections. Conclusions: Non-infectious post-biopsy complications were more frequent than infectious ones in this cohort. Higher post-voiding residual volumes and PSA density, that indicates prostate enlargement, were identified as risk factors and interpreted as secondary to bladder outlet obstruction. The higher body mass index and ethnicity were also identified as risk factors and attributed to the heterogeneity of the patients included. Level of evidence: Not applicable for this multicentre audit.